Pindstrup Mosebrug i hundrede år. En studie i forretningsudvikling - Pedersen, Kurt; Strandskov, Jesper; Sørensen, Peter (Historisk Tidsskrift, 2013)
Pindstrup Mosebrug 1905-2005. A Study in Business DevelopmentPindstrup Mosebrug, the leading Danish producer of sphagnum, a growing medium for plants, is recognized far beyond Denmark’s borders as it serves demand on a global scale from a number of European production sites. This article describes and analyses how the firm acquired its position from a modest start in 1905. The century-long story centres on the exploitation of an increasingly scarce resource, peat. Johannes la Cour, the founder, owner and manager, was acutely aware of the scarcity of good peat bogs and ceaselessly acquired bogs whenever they were available. His focus was on the use of peat for heating purposes, but all along he saw opportunities for diversification of the resource and actually initiated new lines of business. Peat was by no means an ideal fuel, however, and, as a result, demand followed changes in the accessibility of coal (and, later, oil). The two world wars predictably offered golden business opportunities to Pindstrup Mosebrug, the war years thus proving highly profitable. The interwar period was a challenge, however: having gone almost bankrupt, the firm was reconstructed. During the Post-World War Two period, the funds accumulated proved insufficient to sustain the company, making it clear that the days of peat as a fuel had come to an end. In the mid-fifties, Bertel Stausholm, the founder’s son-in-law, gradually took over and tried his hand at a variety of related as well as unrelated diversifications, including wood industry and ceramic tiles. What saved the company, however, was the change in the use of peat – from serving as a fuel it became a growing medium used by both private and professional gardeners. In 1971, a new co-manager, Niels Søe, was appointed, who became the man aging director of Pindstrup Mosebrug in 1985. Although the firm had developed international relations over the years, it was due to Søe that the operations of the firm were radically internationalized on both the sourcing and marketing sides. Targeting new customer groups, he initiated continuous product and process development turning peat into a high value material. This article outlines the development of a company which over a period of a hundred years had merely three CEOs, each of whom represented a distinct strategic profile. The long firm history may be summarized in a fairly simple schedule: Focus – crisis – diversification – crisis – re-focus. Through the stages runs a connecting thread, viz. a penetrating understanding of the substance of bogs. Translated by Margrethe Petersen